Cancer patients’ preferences for either quality of life or a longer life determine their willingness to talk about forgoing cancer-specific treatment - Laryionava, Katsiaryna; Hartmann, Mechthild; Sklenárová, Halina; Jäger, Dirk; Winkler, Eva C. (Oncology research and treatment, 2019)
Background: Cancer patients often face decisions whether to proceed with cancer-specific treatment or to switch to best supportive care. In these decisions, patients’ preferences should be determining cornerstones. The aim of this survey was to elicit patients’ preferences regarding discussions about forgoing treatment and factors influencing their preferences. Methods: We surveyed 194 patients at the National Center for Tumor Diseases, Germany. Quality of life (FACT-G), cancer-specific distress (QSC-R10), anxiety/depression (PHQ-4/GAD-2), preferences regarding quality/length of life (QQ), patient-physician communication (CARES-SF), and family role (CCAT-P) were assessed. Results: Patients weighting quality of life over lifetime wanted their oncologists to address treatment limitations as early as possible (p = 0.00). Patients striving for a longer lifetime did not want such discussions (p = 0.05). Having discussed treatment limitations was not associated with increased anxiety, depression, or distress. Limiting treatment was discussed only with one-third of the patients with a prognosis of less than 6 months and rather with elderly patients or patients in a worse medical condition. Attributing an important role to family decisions was associated with striving for lifetime (p = 0.01). Conclusion: Preferences for either quality or length of life were associated with patients’ willingness to discuss forgoing cancer-specific treatment. Timely discussion of realistic treatment goals is one way to avoid overtreatment. Patients striving for lifetime require increased attention and opportunities to address prognosis and risks of treatment.